Political and institutional determinants of the cyclicality of fiscal policy: evidence from the OECD and Latin America - Venes, Nuno (2010)
In this paper, we analyse the role of political and institutional variables on the cyclical patterns of central government expenditure and revenue. Working with a sample of 38 OECD and Latin-American countries in 1960-2003, we find that higher levels of income inequality are associated with stronger expenditure procyclicality, and that better institutions do not seem to mitigate this effect. IMF interventions are, in general, statistically insignificant in explaining the cyclical behaviour of expenditure, as well as the degree of development of financial systems. On the revenue side, income inequality leads to less procyclical policies. In general, political and institutional variables explain the cyclicality of government expenditure better than that of revenue.